Оптимизационная модель для планирования сетей 5-го поколения - Бондаренко, О. С. (ХНУРЕ, 2020)
The transition to 5th generation communication standards is not an instantaneous process. It requires careful preparation and preliminary planning. It is necessary to update both the data transmission network and the subscriber radio access network, and since the transition process will be carried out within the network serving subscribers, it is necessary to develop an approach allowing to make network resource updates invisible for customers and with minimal costs for mobile operators.